Development of diosir media (water cycle diorama) to improve science literacy of elementary/MI students - Rizky, Putri; Anas, Nirwana (ARKA INSTITUTE, 2025)
Science literacy is a very important skill for students, especially in today's information age, where understanding scientific concepts can affect decision-making in daily life. However, the results of the PISA survey show that science literacy in Indonesia is still relatively low, so a new approach is needed in science learning at the elementary school level. This research aims to develop the Diosir media (water cycle diorama) as a learning tool that can improve the science literacy of grade V elementary school students. The method used is Research and Development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The results of the study showed that the Water Circle Diorama media developed was declared very valid with a percentage of 100% of media experts, 95% of material experts, and 93% of question experts. The practicality of the media was also stated to be very practical with a percentage of 91% of educators and 94% of students. In addition, the classroom trial showed the effectiveness of the media in improving student understanding, with an average pretest score of 69.35 and a posttest score of 94.64, so the increase obtained was 82.06%. In conclusion, the use of water cycle diorama media has been proven to be valid, practical, and effective in improving students' science literacy, as well as being able to increase student involvement in the learning process.